Generasi Muda Melawan Eksploitasi: Studi tentang Kesadaran Hukum Siswa Kelas XI SMAN 4 Pasuruan terhadap Pekerja Anak - Nur Afifah; Uswatul Musarrofah; Ika Yuni Aulia Restanti; Firza Agung Prakoso (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Despite laws prohibiting it, child labor is a significant problem in Indonesia. The root causes of child labor include poverty, lack of public awareness, and ineffective law enforcement. The purpose of this study was to measure the legal understanding of group XI students at SMAN 4 Pasuruan on the issue of child labor. Through a questionnaire given to students, a quantitative descriptive technique was used. The findings of the analysis showed the validity of each questionnaire item and the normal distribution of the remaining data. With a coefficient of determination of 0.554, the regression findings showed a substantial correlation between students' legal knowledge and the decline in child labor, although there was heteroscedasticity. Thus, increasing students' legal knowledge can help reduce the number of child laborers. According to this study, it is important to include legal materials related to child protection into the curriculum and conduct socialization activities to improve students' legal knowledge so that they can actively contribute to the prevention of child labor in the future.